2014
DOI: 10.1177/0272989x14551639
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Numeracy on Verbatim Knowledge of the Longitudinal Risk for Prostate Cancer Recurrence following Radiation Therapy

Abstract: Objective Given the long natural history of prostate cancer we assessed differing graphical formats for imparting knowledge about the longitudinal risks of prostate cancer recurrence with or without therapy. Methods Male volunteers without a history of prostate cancer were randomized to one of eight risk communication instruments that depicted the likelihood of prostate cancer returning or spreading over 1, 2, and 3 years. The tools differed in format (line, pie, bar, or pictograph) and whether the graph als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 27 publications
1
41
1
Order By: Relevance
“…In a Cochrane review (2013) on the value of personalized risk communication, the authors concluded that incorporating personalized risk estimates increases knowledge, may increase accuracy of risk and enhance informed choices, but may not significantly affect an individual’s anxiety [14,50]. However, identifying women who are anxious or worry about recurrence and simultaneously managing their worry with supportive care while correcting misconceptions about recurrence risk seems like a reasonable approach [21,24,51]. Our findings do suggest that physicians are more likely to inquire about worry among women who themselves report the most worry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Cochrane review (2013) on the value of personalized risk communication, the authors concluded that incorporating personalized risk estimates increases knowledge, may increase accuracy of risk and enhance informed choices, but may not significantly affect an individual’s anxiety [14,50]. However, identifying women who are anxious or worry about recurrence and simultaneously managing their worry with supportive care while correcting misconceptions about recurrence risk seems like a reasonable approach [21,24,51]. Our findings do suggest that physicians are more likely to inquire about worry among women who themselves report the most worry.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings do suggest that physicians are more likely to inquire about worry among women who themselves report the most worry. Notably, many oncologists and surgeons report lack of confidence in managing worry about recurrence with their patients [12,24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, interference with DNA repair via PARP inhibition using Olaparib (AZD 2281) or Niraparib (MK 4827) may initially sensitize cells via increased autophagy and senescence, but not apoptosis. However, this strategy does not appear to interfere with proliferative recovery, which could, in theory, contribute to disease recurrence [3437]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite previous research testing pictographs against other graphic formats, only little attention has been paid to the question of how exactly these pictographs should look, and thus which icon type to use in a pictograph. Thus, pictographs include a variety of icon types for displaying risks, without a scientific basis for whether the concreteness of the iconicity in pictographs facilitates or impedes the comprehension of medical risk information.…”
Section: Introductionmentioning
confidence: 99%